How to repair a small umbilical hernia laparoscopically. Issue 11 (1st September 2020) - Matthews, Samuel; Lauti, Melanie; Xia, Weisi; Currie, Nicholas; Morrow, Jon
Abstract : We describe a step by step technique for repair of a small umbilical hernia laparoscopically that aims to provide an excellent technical and cosmetic result without a significant increase in operative time or cost. Patients report good quality of life post‐operatively and appear satisfied with the cosmetic result.